Theoretical and methodological foundations for improving technical skills of highly skilled athletes in track and field competitions - Kolot, A.; Sovenko, S.; Rezanov, O. (Journal of Physical Education and Sport, 2025)
At the current stage of athletic development, technical training within long-term improvement system must incorporate clearly defined model characteristics of technical actions and physical fitness. Identifying biomechanical indicators and criteria of technical skills in highly qualified athletes enables the adjustment the training process by considering individual features of competitive performance. This approach facilitates the creation of effective technical training models. Objective: The objective is to improve the technical mastery of elite track and field athletes by establishing clear requirements for their technical fitness level and identifying the key components of technical skill. Material and methods: The data from more than 60 literature sources concerning the structural components of technical skills and the content of technical training of highly qualified track and field athletes at different stages of long-term training have been systematized. An expert survey of 36 coaches who have experience in working with highly qualified athletes was carried out; the documents of the training process planning as well as the diaries of athletes (n=244) were analyzed, and the optimal criteria of technical skill assessment were determined. Video recording and biomechanical analysis of the competitive exercise performance by long jumpers (n=15) and race walkers (n=36) at the stage of specialized basic training, as well as by long jumpers (n=8) and race walkers (n=31) at the stage of maximum realization of individual capabilities were carried out. Results. The basic provisions of improving the technical skills of highly qualified athletes in track and field competitive events are presented. The main structural components and criteria characterizing the technical mastery of athletes at the modern stage are highlighted. The basic biomechanical indices of the technique of motor actions and the level of special physical fitness of athletes at each stage of long-term improvement are established. The dynamics of the competitive practice volume and requirements for the selection of training means of technical orientation are determined. The analysis of scientific and methodical literature resulted in supplementing the data on biomechanical criteria of evaluating the technical skills of highly qualified track and field athletes. Conclusions. The effectiveness of training methods for highly qualified athletes is determined by the transformation of the technical potential accumulated at the previous stages of long term training into the final competitive result. This can be achieved by determining a proper ratio of means and methods of different orientations, where the use of exercises aimed at improving the high level of technical fitness of track and field athletes will be the key one. Technical mastery as an integral criterion of the athlete's highest level of fitness allows to achieve maximum results in conditions of tough competition due to perfect mastery of the most rational motor structures of sports exercises.